Socialscape Ecology: Integrating Social Features and Processes into Spatially Explicit Marine Conservation Planning - Baker-Médard, Merrill; Concannon, Katherine; Gantt, Courtney; Moen, Sierra; White, Easton R. (Sustainability, 2024)
Conservation planning is the process of locating, implementing, and maintaining areas that are managed to promote the persistence of biodiversity, ecosystem function, and human use. In this review, we analyze the ways in which social processes have been integrated into Marxan, a spatially explicit conservation planning tool used as one step in a broader process to select the location and size of protected areas. Drawing on 89 peer-reviewed articles published between 2005 and 2020, we analyzed the ways in which human activity, values, and processes are spatialized in the environment, something we call socialscape ecology. A socialscape ecology approach to conservation planning considers not only the spatial configuration of human activity in a land or seascape but also the underlying drivers of these activities, how resource use rights and access operate in an area, and how resource users contribute to data collection and decision making. Our results show that there has been a small but statistically significant increase in the total number of cost variables into Marxan analysis over time, with uneven performance across seven of the nine categories assessed. One notable area of improvement has been the increase over time in number of studies integrating socio-environmental change (e.g., climate change) in their analysis. Including accurate, context-specific, and detailed accounts of social features and processes within land and seascapes is essential for developing conservation plans that are cost-effective, ecologically sound, socially desirable, and just.